Multiplicity Dependence of the Jet Structures in pp Collisions at LHC Energies - Zoltán Varga; Róbert Vértesi; Gergely Gábor Barnaföldi (Proceedings, 2019)
We study the charged event multiplicity dependence of the jet structure in pp collisions. We present evidence for jet shape modification due to multi-parton interactions using PYTHIA and HIJING++ Monte Carlo (MC) event generators as an input to our analysis. We introduce a characteristic jet size measure which is independent of the choice of simulation parameters, parton distribution functions, jet reconstruction algorithms and even of the presence or absence of multi-parton interactions. We also investigate heavy-flavor jets and show the sensitivity of the multiplicity-differential jet structure to flavor-dependent fragmentation.